Protected areas and road development: sustainable development discourses in the Annapurna conservation area, Nepal - Kumari Lama, Anu; Job, Hubert (ERDKUNDE, 2014)
Protected Areas (PAs) in developing countries are undergoing a rapid transformation brought about by global-local forces of change. The intensification and extension of these change processes have put those PAs in remote regions at the heart of the sustainable development discourse. Using a qualitative research approach, the current study analyses discourse on the Nepal’s Annapurna Conservation Area (ACA) sustainability from the road development, against the background of the global-local change process. The combined effects of neoliberal economic restructuring and policy reforms, as well as the globalization of local economy induced by the road impacts, have altered governance aspects of the ACA management a lot. The paper also reveals further intensification of localised political economic problems, invigorating the moral dimensions of the PA sustainability. We argue that poverty alleviation for sustainable development needs to move away from the rhetoric of the conventional economic growth narrative. PA sustainability in the context of road development in the ACA should be understood as a broader concept, where political, environmental and socio-economic processes related with the dynamics of global-local change and multilevel governance, play a crucial role. The contemporary PA sustainability debate, in this context, requires understanding the human-environment relationships and their interplay, from a multilevel governance perspective.